(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Tuberculosis (TB) is one of the major public health problems. Sputum microscopy even today is considered as most important laboratory diagnosis of TB though its negative result does not exclude tuberculosis. Objective: To evaluate the smear negative suspected TB patients by GeneXpart. Materials and Methods: This descriptive cross-sectional study was conducted in Surya Kanto Hospital, Mymensingh from September 2014 to September 2016. Total 300 suspected TB patients were selected and sputum microscopy was performed then re-evaluation of the smear negative cases was carried out by GeneXpert. Results: The mean age of the patients was 38.87 ± 13.78 years with a male to female ratio 2.1: 1 and 86% was in economically productive age of life. About 13.1% smear negative suspects were diagnosed as TB positive by GeneXpert. Conclusion: GeneXpert played effective role to re-evaluate the smear negative TB cases. So, GeneXpert may be recommended routinely for TB detection. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 3-6